UPAYA PENINGKATAN MUTU PRODUK RUJAK BUAH (LOTIS) PEDAGANG KAKI LIMA DI PABELAN KARTASURA - Aan Sofyan (WARTA LPM, 2018)
This dedication program is an effort to solve partner problems. Partners coupled in this devotion program is a fruit salad or lotis merchant. The problems faced by partners are lack of knowledge about hygiene and sanitation in food processing (fruit salad/lotis). This condition is seen among others from carts used every day to sell salad/lotis salad. Wooden wagon material with coated paint is a hazardous material for use in food processing. Coat that is used to coat wood is a non-food grade material that can be included in the food sold. The purpose of this IbM program is to help partners improve wagon conditions by designing carts with safer materials by the principle of sanitation and food safety in food processing. Also, the purpose of this program is to increase knowledge about hygiene and sanitation for partners; this is done by providing reading media in the form of booklets that contain guidelines on the application of the principles of hygiene, sanitation and good food security in food processing. The next goal is to raise awareness of the partners always to maintain personal hygiene so that the opportunities of contamination from humans to food can be reduced or eliminated.